Ergonomics in Practice and its Influence on Employees´ Performance - Luboslav Dulina; Miroslava Bartanusova (Communications - Scientific letters of the University of Zilina, 2014)
The article deals with the human performance and the factors that affect job performance. During the performance of work a person is exposed to risk factors which to some extent adversely affect his health. It is necessary to note that two views of the position of man in the process currently prevail in the company. The first one, promoted by particular employers, puts the emphasis on performance increase of workers and productivity growth. The second one view is supported by employees and emphasizes the need for safety of a man and health at work. The aim of ergonomics is currently referred to harmonise these views.